Pengaruh Fasilitas Kantor, Disiplin Kerja, Dan Kompetensi Pegawai terhadap Kualitas Pelayanan - Kurniasari, Riyanti Ratna Ayu; Oktarina, Nina (Universitas Negeri Semarang, 2020)
The purpose of this study is to determine wheter there is a positive and significant influence of office facilities, work discipline, and employee competence on service quality in east Semarang District Office Semarang City simultaneously or partially. The population of this research is users of office services in the east semarang district office semarang city. The research sample was 115 respondents. This study uses a quantitative approach and data collection using a questionnaire. The data analysis method used is descriptive analysis, multiple linear regression, and hypothesis testing. The method of data analysis is descriptive analysis, linear regression and hypothesis test. The results of multiple regression analysis in this study are Y= 6,782 + 0,567FK + 0,436DK + 0,323KP + e.